ANALISIS JALUR FAKTOR-FAKTOR YANG MEMPENGARUHI KETAHANAN PANGAN RUMAH TANGGA DI KABUPATEN LEBAK, PROPINSI BANTEN - Ikeu Tanziha; Eka Herdiana (Food and Nutrition Society of Indonesia, 2009)
The objective of the study was to analyze direct and indirect factors that influence household’s food security. The study design was a crosectional study. Research was conducted in Pasindangan and Banjarsari Village, Cileles and Warunggunung Subdistrict, Lebak Distric, Banten Province in April - May 2009. A purposive sampling was applied to select 101 households. The data collected include socio economy and food intake. Quantitatively,a household is categorized as food security, if his/her TKE >90%, and a household is categorized as food insecurity, if his/her TKE < 90%. The Rank Spearman test was applied to analyze correlation of socioeconomic, demographic and food intake variables between food securities. Path analysis was used to analyze direct and indirect factors that influence household’s food security. The results showed that 62.4% households were food security, and 37.6% households were food insecurity. There are correlation between household expenditure per capita, number of household member and land area to household food security. Based on the path analysis,direct factor that influence household food security was household expenditure per capita. Indirect factors that influence household food security were number of household member – household expenditure per capita – household food security.